Interaksi Teknologi dan Tenaga Kerja: Peran Teknologi pada Daya Saing Produk (Studi Kasus Sentra Usaha Kecil dan Menengah Bordir Bangil Pasuruan) - Nur Faiza; Anita Kristina (Jurnal Maksipreneur, 2021)
The purpose of this study is to analyze the role of technology in the production situation for competitiveness in small embroidery industries. It also relates to the analysis of choices for the use of technology and changes in the workforce situation. The study was conducted at the small embroidery industrial center in Bangil, Pasuruan, East Java, Indonesia. Data collection through in-depth interviews with informants business owners and workers. A qualitative phenomenological approach was used in this study. Data is processed and analyzed inductively. The findings are obtained that the technological needs in the production process cannot be avoided due to efforts to improve product competitiveness. The impact of these efforts forced business owners to rethink and manage their technology and workforce needs. The provision of technology is the main skill for workers so that workers also make efforts to improve the quality of embroidery with computer machines and complete orders on time. The implication of this research is expected to be able to provide enrichment in understanding the concept of sustainability of small businesses which is focused on the issue of choice of technology use and labor use.